The Effects of acaricidal and insecticidal activities on working suspension of Creolin-x - Altangerel, Khuntsetseg; Narantuya, Ochir; Bayandulam, Dorjnamjim; Oidov, Narantuya; Purevdorj, Tserenlkham; Tuya, Saranchimeg; Bazartseren, Boldbaatar; Nergui, Davaasuren; Bayasgalan, Chimedtseren; Tserendorj, Ariunaa; et al. (Mongolian Journal of Agricultural Sciences, 2022)
To determine the acaricidal and insecticidal activities of working suspension of Creolin-X preparation in vitro, we collected suspension samples from a 3-ton tank before and after dipping every 200th sheep; acaricidal activity was calculated using Abbot’s (1978) formula. During the dipping process, the working solution was not freshly prepared; rather, once the suspension volume was decreased post-dipping, we added water and Creolin-X at a 1:1000 ratio to fix the liquid volume deficit. Before the dipping process, the acaricidal activity of CREOLIN-X working suspension was 100% effective against Psoroptes cuniculi within 24 hours. The acaricidal activity was changed to 92.2±1.8% after dipping the 200th sheep, 78.4±5.4% after dipping the 400th sheep, 63.8±1.1% after dipping the 1400th sheep, and 35.6±1.1% after dipping the 2810th sheep. The same results were found when the suspension solution was used against Haematopinus, Bovicola spp. The insecticidal activity was 100% before dipping any sheep, and 95%, 85%, and 45% after the same number of respective sheep mentioned in the prior were dipped. The results showed that the number of sheep affects the acaricidal activity, even though the acaricidal activity increased by 13.5-17.7% after adding the 1:1000 ratio of water and Creolin-X working solution once the suspension volume had been reduced. Further studies are required to study different ectoparasites. Креолин-х бэлдмэлийн ажлын цийдмэгийн хачиг, шавж үхүүлэх идэвхийг судалсан дүн Хураангуй Үйлдвэрлэлийн нөхцөлд 3 тонны багтаамжтай ваннанд бэлтгэсэн Креолин-Х бэлдмэлийн угаалгын ажлын цийдмэгийн дээжээс хонь угаахаас өмнө болон 200 хонь угаах бүрд авч, хачиг-шавж үхүүлэх идэвхийг in vitro орчинд туршин сорьж үр дүнг Абботын (1978) томьёогоор тогтоов. Угаалгын явцад ванн дахь ажлын цийдмэгийг шинээр найруулж бэлтгээгүй, харин дундарсан цийдмэгийг 1:1000 (бэлдмэл:ус) харьцаагаар сэлбэв. Хонь угаахын өмнөх Креолин-Х бэлдмэл (циперметрин 5%)-ийн угаалгын ажлын цийдмэгт P.cuniculi хачгийг үйлчлүүлэхэд 24 цагт 100±0% үхүүлэх идэвхтэй байв. Харин Креолин-Х бэлдмэлийн угаалгын ажлын цийдмэгт 200 хонь угаасны дараа хачиг үхүүлэх идэвх 92.2±1.8%, 400 хонь угаахад 78.4±5.4%, 1400 хонь угаахад 63.8±1.1%, 2810 хонь угаасны дараа 35.6±1.1% болсон байна. Дээрх нөхцөлд Креолин-Х бэлдмэлийн угаалгын ажлын цийдмэгийн шавж үхүүлэх идэвхийг Haematopinus, Bovicola төрлийн ширхэнд туршин сориход угаахын өмнө 100%, угаасны дараа доорх дарааллаар 95%, 85%, 45% шавж үхүүлэх идэвхтэй байна. Креолин-Х бэлдмэлийн ажлын дундарсан цийдмэгийг 1:1000-аар сэлбэсний дараа хачиг-шавж үхүүлэх идэвх 13.5-17.7%-аар өсдөг ч угаасан хонины тооноос хамаарч өөрчлөгдөх эрсдэлтэй. Цаашид энэ судалгааг өөр хачиг, шавж дээр үргэлжлүүлэх шаардлагатай. Түлхүүр үг: Креолин-Х цийдмэг, гадна шимэгч, Хонь, шавьж устгах шинж чанар